2016
DOI: 10.5588/ijtld.15.0928
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease and risk factors for death among children treated for tuberculosis in Malawi

Abstract: SUMMARY SETTING Tuberculosis is a leading cause of childhood death. There is limited patient-level data on pediatric TB in Malawi that can be used to guide programmatic interventions. OBJECTIVE To describe pediatric tuberculosis case burden, disease pattern, treatment outcomes, and risk factors for death and poor outcome. DESIGN We conducted a retrospective cohort study utilizing routinely collected data in treatment registers. Odds ratios for factors associated with poor outcome and death were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
7
17
3
Order By: Relevance
“…[ 12 ] In Malawi, a nation-wide survey of programme data in 1998 reported that 17% of the children died; [ 13 ] while analysis of 3-year (2011–2013) programme data from treatment centres in central Malawi reported 9.5% deaths. [ 14 ] Likely inclusion of more severe cases with higher mortality risk, would at least in part explain the difference between these studies and our findings.…”
Section: Discussioncontrasting
confidence: 77%
“…[ 12 ] In Malawi, a nation-wide survey of programme data in 1998 reported that 17% of the children died; [ 13 ] while analysis of 3-year (2011–2013) programme data from treatment centres in central Malawi reported 9.5% deaths. [ 14 ] Likely inclusion of more severe cases with higher mortality risk, would at least in part explain the difference between these studies and our findings.…”
Section: Discussioncontrasting
confidence: 77%
“…We found that more than one-quarter of children with TB in Kenya were HIV infected, which is slightly lower than the 31% co-infection rate among adults with TB in Kenya and the 32% co-infection rate reported in a sample of Malawian children with TB, 19,20 but still substantial. Prevention of TB among HIV-infected children is a key priority in Kenya.…”
Section: Discussioncontrasting
confidence: 73%
“…27 However, unlike a study from Malawi, we did not find that children on ART at the time of starting TB treatment were more likely to die than children who initiated ART after being diagnosed with TB. 20 The use of ART among TB/HIV co-infected children reduces morbidity and mortality. 22,28 Our observation that HIV-infected children on ART still had nearly 4 times the likelihood of death as HIV-negative children could be due to early mortality among children who were started on ART when their disease was already advanced, virologic failure, immune reconstitution syndrome, or poor adherence to ART.…”
Section: Discussionmentioning
confidence: 99%
“…Attention should also be paid toward LTFU among certain special populations. The proportion of LTFU among childhood TB patients ranges from 4 to 37% [52][53][54][55][56][57]. Among the children with drug-resistant TB, it ranges from 5 to 19.09% [58][59][60].…”
Section: Proportion Of Ltfumentioning
confidence: 99%